Molecular Characterization of a Rare Dedifferentiated Liposarcoma With Rhabdomyosarcomatous Differentiation in a 24 Year Old. (June 2020) - Olson, Nicholas; Gularte-Mérida, Rodrigo; Selenica, Pier; Da Cruz Paula, Arnaud; Alemar, Barbara; Weigelt, Britta; Lefferts, Joel; Linos, Konstantinos
Aims . The aim of this study was to identify potential driver genetic alterations in a dedifferentiated liposarcoma (DDLPS) with rhabdomyosarcomatous differentiation. Methods and Results . A 24-year-old female underwent resection of an abdominal mass, which on a previous biopsy demonstrated rhabdomyosarcomatous differentiation concerning for embryonal rhabdomyosarcoma. Histologically the resected tumor displayed a high-grade sarcoma with rhabdomyosarcomatous differentiation in the background of well-differentiated liposarcoma consistent with DDLPS. Fluorescence in situ hybridization confirmed MDM2 amplification, as did array-based copy number profiling. Whole-exome sequencing revealed a somatic FGFR1 hotspot mutation and RNA sequencing an LMNB2-MAP2K6 fusion only within the dedifferentiated component. Conclusions . This study represents an in-depth examination of a rare DDLPS with rhabdomyosarcomatous differentiation in a young individual. Additionally, it is also instructive of a potential pitfall when assessing for MDM2 amplification in small biopsies. Despite exhaustive analysis, mutation and gene copy number analysis did not identify any molecular events that would underlie the rhabdomyoblastic differentiation. Our understanding of what causes some tumors to dedifferentiate as well as undergo divergent differentiation is limited, and larger studies are needed.